Poética del cuento hispanoamericano - SERRA, Edelweis (UNIVERSIDAD NACIONAL DE ROSARIO, 1994)
Incluye análisis de :BORGES, Jorge Luis; Cortázar, J.; Benedetti, M.; Carpentier, A.; Rulfo, J.; GARCIA MARQUEZ, Gabriel; Onetti, J.C. etc.